Macroeconomic Determinants of Per Capita Consumption in Indonesia: Evidence from 19902023 Using an ECM Framework - Prawoto, Nano (Universitas Syiah Kuala, 2025)
This study aims to examine the impact of GDP per capita, exchange rate (ER), and broad money (BM) on per capita consumption in Indonesia over the period 19902023. The data were obtained from the World Development Indicators (WDI), and the analysis was conducted using the Error Correction Model (ECM) to capture both short-term dynamics and long-term equilibrium relationships. The findings reveal that, in the long run, GDP per capita and exchange rate significantly influence per capita consumption, while broad money has no statistically significant effect. In the short run, only GDP per capita shows a significant impact. The error correction term (ECT) value of -0.490507 indicates a moderate speed of adjustment towards long-run equilibrium, suggesting that approximately 49% of the disequilibrium is corrected annually. This research contributes to empirical literature by providing updated evidence on macroeconomic determinants of household consumption in a developing country context, using a long-term dataset with rigorous econometric techniques. From a policy perspective, the findings underscore the importance of stable economic growth and prudent exchange rate management in sustaining household welfare through consumption. Policymakers should focus on maintaining macroeconomic stability, particularly through growth-enhancing and inflation-controlling measures, to ensure steady improvements in per capita consumption.